ANALISIS SOCIAL MEDIA MARKETING SEBAGAI STRATEGI PEMASARAN BREWHAVIOR - Haryani, Dwi Septi; Ratnasari, Sri Langgeng; Fauzar, Selvi; Fenny, Fenny; Abriyoso, Octojaya; Elvira, Mita (STIE PEMBANGUNAN TANJUNGPINANG, 2025)
Social media has now become a vital component in the transformation process. This situation opens up great opportunities for MSMEs to utilize social media as a primary tool in marketing activities. The purpose of this study is to understand how Brewhavior utilizes social media as a digital marketing strategy, analyze the use of social media in reaching consumers, and the types of content used, as well as to identify the impact of social media usage on brand awareness growth and sales increase. The research method used is qualitative with a descriptive approach. Data collection techniques are conducted through semi-structured interviews and library studies. The sample in this study is Mr. NHN, the owner of Brewhavior Coffee Shop. The research results indicate that Brewhavior's use of Instagram as an independent digital marketing strategy is capable of increasing brand awareness and sales. Visual content such as Reels, Stories, and direct interaction with customers has proven effective in creating organic promotion and building consumer loyalty. Despite facing resource limitations, this strategy still provides a positive impact on business growth. Moving forward, Brewhavior plans to expand its reach through other platforms such as TikTok to strengthen its brand identity.